Pre-crime: pre-emption, precaution and the future - McCulloch, Jude (Routledge frontiers of criminal justice, 2016)
Introduction: pre-crime : pre-emption, precaution and the future -- Before pre-crime -- Risking the future : pre-emption, precaution and uncertainty -- Pre-empting justice : pre-crime, precaution and counterterrorism -- Pre-crime science, technology and surveillance -- Evidence to intelligence : justice through the crystal ball -- Creating terror : pre-crime, undercover agents and informants -- Pre-crime : securing a just future